EXAMINING THE TREND, THEMES, AND SOCIAL STRUCTURE OF THE ISLAMIC ACCOUNTING USING A BIBLIOMETRIC APPROACH - Muhamad Wahyudi; Sri Herianingrum; Ririn Tri Ratnasari (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2022)
This study focuses on bibliometric indicators of Islamic accounting research development, such as trends in Islamic accounting research and its distribution, topics and themes in Islamic accounting research, significant contributors to Islamic accounting research, the pattern of collaboration in Islamic accounting research, and the most significant texts in the Islamic accounting literature. Four hundred eighty-three pieces of scientific literature were entered into the Scopus database for bibliometric analysis on January 10, 2022. Various programs were used to analyze frequency, metrics, and citations, including Microsoft Excel, VOS viewer, and Harzing's Publish or Perish. Over the last ten years, Islamic accounting publications have grown significantly and steadily. Islamic accounting literature is based in Asia, Europe, America, and the Middle East, and it can be found in social science, business, management, accounting, economics, and finance. With a few exceptions in Malaysian, Arabic, German, Indonesian, Slovak, and Turkish, the majority of Islamic accounting literature is written in English. The study also discovered that terms like Islamic bank, banking, Islamic performance, Islamic accounting standards, and Islamic finance are commonly used. The seven countries that contributed the most to the development of scholarly collaborations in Islamic accounting were Malaysia, Indonesia, the United States, Saudi Arabia, the United Kingdom, Pakistan, and Australia. This is critical in assisting academics in making recommendations for future study in the field of Islamic accounting.